Cuttlefish skin papilla morphology suggests a muscular hydrostatic function for rapid changeability. (2nd February 2013) - Allen, Justine J.; Bell, George R. R.; Kuzirian, Alan M.; Hanlon, Roger T.
Abstract Coleoid cephalopods adaptively change their body patterns (color, contrast, locomotion, posture, and texture) for camouflage and signaling. Benthic octopuses and cuttlefish possess the capability, unique in the animal kingdom, to dramatically and quickly change their skin from smooth and flat to rugose and three‐dimensional. The organs responsible for this physical change are the skin papillae, whose biomechanics have not been investigated. In this study, small dorsal papillae from cuttlefish (Sepia officinalis) were preserved in their retracted or extended state, and examined with a variety of histological techniques including brightfield, confocal, and scanning electron microscopy. Analyses revealed that papillae are composed of an extensive network of dermal erector muscles, some of which are arranged in concentric rings while others extend across each papilla's diameter. Like cephalopod arms, tentacles, and suckers, skin papillae appear to function as muscular hydrostats. The collective action of dermal erector muscles provides both movement and structural support in the absence of rigid supporting elements. Specifically, concentric circular dermal erector muscles near the papilla's base contract and push the overlying tissue upward and away from the mantle surface, while horizontally arranged dermal erector muscles pull the papilla's perimeter toward its center and determine its shape. Each papilla has a white tip, which is produced by structural light reflectors (leucophores and iridophores) that lie between the papilla's muscular core and the skin layer that contains the pigmented chromatophores. In extended papillae, the connective tissue layer appeared thinner above the papilla's apex than in surrounding areas. This result suggests that papilla extension might create tension in the overlying connective tissue and chromatophore layers, storing energy for elastic retraction. Numerous, thin subepidermal muscles form a meshwork between the chromatophore layer and the epidermis and putatively provide active papillary retraction. J. Morphol., 2013. © 2013 Wiley Periodicals, Inc.